Gestión, Procesos Y Calidad Universitaria: Caso Ecuatoriano - Yépez, Carlos Ricaurte; Pozo, José Manuel (European Scientific Journal, ESJ, 2018)
The objective of this study was to conduct a critical analysis of university management; for this, secondary information was collected from various bibliographic sources, and the respective analysis and contributions were carried out based on the knowledge acquired. The article deals with the currents and administrative theories, principles about the quality, functions and processes that are carried out in the university and the evolution of this as organizational and academic structure, within a determined historical context, management models, in relation to the management process.